KAJIAN TINGKAT KEMATANGAN KESELARASAN STRATEGI BISNIS DAN TI DENGAN MENGGUNAKAN METODE LUFTMAN STUDI KASUS: PT. BIT TEKNOLOGI NUSANTARA - Handayani, Rani Irma (Jurnal Pilar Nusa Mandiri, 2016)
PT . BIT Technology Nusantara is a company engaged in telecommunications . In its operations the company is in dire need of Information Technology ( IT ) to solve daily operational tasks . Even at this time Information Technology (IT ) plays an important role in enhancing the perceived competitive advantage of an organization. IT has proven to create value for the organization. Organizations are increasingly dependent on IT to remain competitive with other organizations. With the right IT management expected the application of information technology can run optimally. Good IT management is done by assessing the compatibility between the application of IT and business processes of the organization. For that Luftman method is used for measuring the alignment of business and IT strategy by using six criteria: Communicationz, Competency / Value Measurement, Governancz, Partnership, Scopes & Architecture, Skills.